Tentang Kata Korupsi yang Datang Silih Berganti: Suatu Penjelasan Budaya - Muhammad Nasrum (Antropologi Indonesia, 2013)
This paper is intended to provide an overview of anthropological perspectives on corruption as political, social, and cultural phenomenon. The author attempted that anthropological concerns on corruption was driven by a number of epistemological reasons, institutionalized and embedded in the broader context of power relations both of globally and locally. The biggest challenge for anthropology, which deals with the complexity of corruption, lies in: how to explain or interpret such phenomenon without apprehensively will be going into ethical and moral pitfalls. On the one hand anthropologists should be described corruption as an inevitable part of wider power relations at the heart of the state and the law, where in many cases are not clearly demarcated or intentionally obscured; and the other, there was a need of a reflexive anthropological understanding which traditionally always been trying to understand the rules and norms of social orders as a cultural framework.Key-words: corruption, culture, anthropologist, anthropology, power, state